Influence of voice focus on tongue movement in speech - Bressmann, Tim; Boer, Gillian de; Castro Marino, Viviane Cristina de [UNESP]; Gradim Fabron, Eliana Maria [UNESP]; Berti, Larissa Cristina [UNESP] (Taylor & Francis Inc, 2017)
The present study evaluated global aspects of lingual movement during sentence production with backward and forward voice focus. Nine female participants read a sentence with a variety of consonants in a normal condition and with backward and forward voice focus. Midsagittal tongue movement was recorded with ultrasound. Tongue height over time at an anterior, a central, and a posterior measurement angle was measured. The outcome measures were speech rate, cumulative distance travelled, and average movement speed of the tongue. There were no differences in speech rate between the different conditions. The cumulative distance travelled by the tongue and the average speed indicated that the posterior tongue travelled a smaller cumulative distance and at a slower speed in the forward focus condition. The central tongue moved a larger cumulative distance and at a higher speed in the backward focus condition. The study offers first insights on how tongue movement is affected by different voice focus settings and illustrates the plasticity of tongue movement in speech.
Keywords: Articulation; tongue movement; ultrasound; voice focus